Lessons Learned from Managing Electronic Sow Feeders and Sow Body Weight Data - L. L. Thomas; S. S. Dritz; M. D. Tokach; R. D. Goodband; J. M. DeRouchey; J. C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2016)
As the swine industry is transitioning from individual gestation stalls to different styles of group housing, new challenges are being presented for collecting data in the gestation barn. Electronic sow feeders (ESF) are computerized feeding stations that track and dispense feed for each sow that enters the feeding station. Individual intakes for sows can be recorded, which creates an opportunity for conducting nutrition studies in gestation. A research study was conducted on a commercial sow farm in central Nebraska, where sows were group-housed with ESF. A total of 74,114 feed intake observations and 663,204 sow weights were recorded during the study. Feed intakes were downloaded daily, with unknown errors occurring during download 13 of 149 days. Intakes had to be downloaded prior to the system reset each day or the previous data would be deleted. Zeroes observed as feed intake values indicated the sow walked through the system, but did not consume any feed. Weights were automatically recorded and stored in system software for multiple weeks at a time. Numerous challenges were presented when attempting to determine accurate sow weights generated from this system, thus two weights were manually collected on all sows and used as reference weights. The reference weights were applied to the data set to eliminate inaccurate weights based on expected weight gains. Using these data, we found that even with adequate training, parity 1 sows were reluctant to consume the assigned feed allowance immediately after placement into the pen as well as throughout the course of gestation. Parity 2 and 3+ sows had similar struggles immediately after placement. It is unknown what could be causing this type of behavior, however, as we continue to generate research within these types of feeding systems, we will continue to
Keywords: sow; electronic sow feeders